FDA orphan drug designations for lysosomal storage disorders: a cross sectional analysis - Garbade, Sven; Zielonka, Matthias; Mechler, Konstantin; Kölker, Stefan; Hoffmann, Georg F.; Staufner, Christian; Mengel, Eugen; Ries, Markus (medRxiv, 2020)
Purpose To provide a quantitative clinical-regulatory insight into the status of FDA orphan drug designations for compounds intended to treat lysosomal storage disorders (LSD’s). - Methods Assessment of the drug pipeline through analysis of the FDA database for orphan drug designations with descriptive and comparative statistics. - Results Between 1983 and 2019, 124 orphan drug designations were granted by the FDA for compounds intended to treat 28 lysosomal storage diseases. Orphan drug designations focused on Gaucher disease (N=16), Pompe disease (N=16), Fabry disease (N=10), MPS II (N=10), MPS I (N=9), and MPS IIIA (N=9), and included enzyme replacement therapies, gene therapies, and small molecules, and others. Twenty-three orphan drugs were approved for the treatment of 11 LSDs. Gaucher disease (N=6), cystinosis (N=5), Pompe disease (N=3), and Fabry disease (N=2) had multiple approvals, CLN2, LAL-D, MPS I, II, IVA, VI, and VII one approval each. This is an increase of nine more approved drugs and four more treatable LSD’s (CLN2, MPS VII, LAL-D, and MPS IVA) since 2013. Mean time between orphan drug designation and FDA approval was 89.7 SD 55.00 (range 8-203, N=23) months. - Conclusions The development pipeline is growing and evolving into diversified small molecules and gene therapy. CLN2 was the first and only LSD with an approved therapy directly targeted to the brain. Newly approved products included “me-too” - enzymes and innovative compounds such as the first pharmacological chaperone for the treatment of Fabry disease.